Heuristic algorithm for university scheduling - De La Pena, Fortunato T. (1976)
This work deals with the problem of scheduling courses in the university. An algorithm which basically follows the pattern used by experienced schedulers was designed to take care of assigning time slots to courses that are to be offered. The procedure employs the use of heuristic decision rules to reach a satisfactory, but not necessarily optimal, solution. A guide for deriving course enrollment forecasts was also developed to provide the input for the scheduling process. This forecasting procedure is based on the application of course attrition rates to advanced advising tallies. The study concluded with an investigation as to the possibility of deriving deterministic enrollment forecasts and improving registration procedures through the use of programmed advising.
Mimeographed.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman.
Keywords: Scheduling (Management).; Algorithms